Perancangan Apartemen Mahasiswa dengan Pendekatan Biophilic Design di Dramaga Bogor (Jurnal TekstuReka, 2023)
The existence of the Bogor Agricultural Institute (IPB), has become one of the factors of the fast development in Dramaga District of Bogor. Dramaga's development can be seen from the growth of vertical commercial and residential buildings. The growth of vertical housing is based on the purpose of marketing to IPB students. Along of recent years, IPB students have increased which makes the rental housing market compete to provide residential facilities as Student Apartments. The growth number of IPB students was not followed by the growth of rental housing. Based on the research results, there are students who carefully decide where they want to live along their study. The Biophilic Design approach, being able to participate helps connect activity users (residents, managers, and visitors) to be active in social interaction. Not only the relationship between humans but also as an access to the relationship between humans and nature. Biophilic Design can also reduce student stress caused by activities while studying. The method in this research is direct observation, literature review and design analysis with the results of concrete concepts. This research provides a solution for meeting the needs of housing with a typology of forms and spatial patterns that provide a sense of connection with nature.